2018
DOI: 10.3389/fpsyg.2018.00208
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Plus Reflection Training: Effects on Executive Function in Early Childhood

Abstract: Executive function (EF) skills are essential for academic achievement, and poverty-related stress interferes with their development. This pre-test, post-test, follow-up randomized-control trial assessed the impact of an intervention targeting reflection and stress reduction on children's EF skills. Preschool children (N = 218) from schools serving low-income families in two U.S. cities were randomly assigned to one of three options delivered in 30 small-group sessions over 6 weeks: Mindfulness + Reflection tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 64 publications
4
100
1
2
Order By: Relevance
“…There were no significant differences on any measure of executive functioning although small sample size and lack of validated measures may have reduced the opportunity to determine if the program was helpful. Zelazo et al (2018) found that children who were randomly assigned to a mindfulness plus reflection training program significantly outperformed the business-as-usual (BAU) group in direct behavioral assessments of EFs, with differences most pronounced at the 4–6 week follow-up testing. Off (2018), in an unpublished dissertation, undertook an evaluation of MindUP in children ( N = 159) in 15 Kindergarten classrooms across eight schools using a pre–post design.…”
Section: Introductionmentioning
confidence: 98%
“…There were no significant differences on any measure of executive functioning although small sample size and lack of validated measures may have reduced the opportunity to determine if the program was helpful. Zelazo et al (2018) found that children who were randomly assigned to a mindfulness plus reflection training program significantly outperformed the business-as-usual (BAU) group in direct behavioral assessments of EFs, with differences most pronounced at the 4–6 week follow-up testing. Off (2018), in an unpublished dissertation, undertook an evaluation of MindUP in children ( N = 159) in 15 Kindergarten classrooms across eight schools using a pre–post design.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have tested the possibility that executive function can be improved in children (and adults) broadly by exercising executive function components on lab tasks or via particular activities thought to require executive function, like switching between two languages, engaging in pretend play, and doing martial arts (Bialystok, 2001;Lillard et al, 2013;Diamond, 2012), or by supporting underlying developmental mechanisms like reflection (e.g., Espinet, Anderson, & Zelazo, 2013;Zelazo, Forston, Masten, & Carlson, 2018). Improvements in executive function components are then expected to lead to improvements in related domains that require executive function (e.g., so-called "transfer").…”
Section: Conceptualizing Executive Function Development As Improvemenmentioning
confidence: 99%
“…Importantly, there may be variation in the cultural knowledge, beliefs, and values that children learn that can support reflection and using executive function in various contexts (Doebel et al, 2019;Lamm et al, 2018;Lillard, 2016;Obradovic, et al, 2019). Thus, instead of training children to reflect during executive function lab tasks (e.g, Espinet, Anderson, & Zelazo, 2013;Zelazo, Forston, Masten, & Carlson, 2018) it may be more fruitful to provide children with experiences that could help them value using control more, which may, in turn, improve their awareness of the need for control in critical moments. Similarly, children who gain extensive concrete experience learning about shape and color dimensions in their preschool classrooms (like children in Montessori preschools) may perform better on the card sort than children in play-based preschools, in part because they are more capable of reflecting on diverse aspects of the task at hand and engaging control accordingly (Lillard, 2016).…”
Section: New Challenges To Developmental Theories Of Executive Functionmentioning
confidence: 99%
“…Likewise, college students could be motivated to use stimulants to achieve higher grades but potentially be jeopardizing their health. In addition, although beyond the scope of this article, other alternatives to mitigate the impact of poverty on cognition and learning abilities should be carefully explored and considered under the right circumstances if such techniques are safe and efficacious ( Hildebrandt et al, 2017 ; Zelazo et al, 2018 ).…”
Section: The Clinical Ideal and Cognitive Enhancersmentioning
confidence: 99%